Synthesis of Nitrogen Doped Carbon and Its Enhanced Electrochemical Activity towards Ascorbic Acid Electrooxidation - Sankararao Mutyala; Mathiyarasu Jayaraman (International Journal of Electrochemistry)
Nitrogen doped carbon, synthesized by a novel way of carbonizing polyaniline in an inert atmosphere at a constant temperature of 800°C, exhibits several unique features. The carbon: nitrogen ratio is found to increase with the treatment duration up to 120 minutes and a mass reduction of 60 wt% is observed with an interesting observation of the retention of the bulk polymer morphology, surprisingly, even after the carbonization process. The electrochemical activity evaluated with potassium hexacyanoferrate and hexamine ruthenium redox systems at a regular time interval helps to tune the catalytic activity. This type of nitrogen doped carbon prepared from polyaniline base exhibits excellent electrocatalytic activity as illustrated by the oxidation of ascorbic acid in neutral medium.